1996
DOI: 10.1083/jcb.134.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Interference with p53 protein inhibits hematopoietic and muscle differentiation.

Abstract: Abstract. The involvement of p53 protein in cell differentiation has been recently suggested by some observations made with tumor cells and the correlation found between differentiation and increased levels of p53. However, the effect of p53 on differentiation is in apparent contrast with the normal development of p53-null mice. To test directly whether p53 has a function in cell differentiation, we interfered with the endogenous wt-p53 protein of nontransformed cells of two different murine histotypes: 32D my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
104
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 61 publications
(98 reference statements)
9
104
2
Order By: Relevance
“…When satellite cells were derived from p53 null mice, allowed to differentiate, and then exposed to MMS, DOXO or MND protection from cell killing was recorded after exposure to DOXO and MND, whereas no effect was observed after MMS treatment (Figure 8a). Muscle cells lacking p53 have a reduced ability to differentiate; 28 however, under our experimental conditions, we were able to achieve a differentiation efficiency above 80%, thus limiting the possible effects of contamination by proliferating cells. To confirm these results, the same experiment was conducted by silencing p53 in satellite cells by short hairpin RNA (shRNA; Figure 8b).…”
Section: Resultsmentioning
confidence: 78%
“…When satellite cells were derived from p53 null mice, allowed to differentiate, and then exposed to MMS, DOXO or MND protection from cell killing was recorded after exposure to DOXO and MND, whereas no effect was observed after MMS treatment (Figure 8a). Muscle cells lacking p53 have a reduced ability to differentiate; 28 however, under our experimental conditions, we were able to achieve a differentiation efficiency above 80%, thus limiting the possible effects of contamination by proliferating cells. To confirm these results, the same experiment was conducted by silencing p53 in satellite cells by short hairpin RNA (shRNA; Figure 8b).…”
Section: Resultsmentioning
confidence: 78%
“…The plasmids PG 13 -CAT and MG 15 -CAT, 15 were generous gifts from B Vogelstein (John Hopkins Oncology Center, Baltimore, MD, USA). CAT assay was performed on cells 12 h after adriamycin (ADR) treatment (1 or 3 m) or 24 h after Ad-p53 infection.…”
Section: Cat Assaymentioning
confidence: 99%
“…12,13 Restoration of wtp53 function in different tumor types has been demonstrated to suppress the transformed phenotype by inducing growth arrest, apoptosis or cell differentiation. 14,15 Studies on glioblastomas have shown that overexpression of wt-p53 suppress cell growth, and induces apoptotic cell death in vitro and in vivo. [16][17][18][19] These findings have rendered p53 a potentially helpful target for gene therapy of brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…10 In this issue, Yang et al propose a role of p53 in the activation of the myogenic differentiation checkpoint that relies on direct repression of myogenin-a MyoD downstream target gene, whose activation is required for myoblast progression toward terminal differentiation into multinucleated myotubes. 11,12 This finding is of particular interest, when considering that in unperturbed myoblasts p53 rather seems to contribute to muscle differentiation, 13,14 as it suggests that in myoblasts the activity of p53 is biased toward inhibiting differentiation by the DNA damage signaling. The authors first discovered the transcriptional repression of myogenin by p53 in the human rhabdomyosarcoma RD cell line.…”
mentioning
confidence: 97%